Impact of Economic and Financial, Construction Technology and Resources, and Project Organizational Culture on Project Performance Studies at PT. PLN UPP Kitring, Centre Part Borneo-1 - Utomo, Kevin Erianto; Hastin Umi Anisah (Open Access Indonesia Journal of Social Sciences, 2021)
Project construction is a dynamic and complex system that involves many parties from the planning stage to the project handover stage. The problems that arise are varied and generally vary from one project to another, but these problems affect project performance. Project performance is assessed from the time of project execution, the quality or quality of the project and the costs used in the construction project. Problems that arise in a project often lead to an extension of the project implementation time, additional project costs and work results that do not match the quality of the agreement. This study aims to determine the influence of the internal and external environment on project performance, especially the electricity system development project in Borneo. Internal and external environmental factors are taken from related studies as well as previous research that has been carried out in various countries and regions. It can be concluded that economic and financial factors (X1), technology factors and construction resources (X2) and project organizational culture factors (X3) are the factors causing project performance problems (Y).